TRADITIONAL SETTLEMENTS AND HOUSING OF THE NORTH-EASTERN KAZAKHS IN THE EARLY RESEARCHES OF KH.A. ARGYNBAYEV (Journal of history, 2024)
The article shows the contribution of the outstanding ethnographer Kh.A. Argynbayev, one of the first scientists in Kazakhstan to study traditional settlements, housing and economic complexes of the Kazakhs of North-Eastern Kazakhstan at the turn of the mid-19th – early 20th centuries. It is noted that they functioned in the conditions of the prevailing economic and cultural type, represented by nomadic and semi-nomadic cattle breeding, as well as the emerging transition to a semi-sedentary and sedentary way of life. Along with the established forms and types of the material culture under consideration, the influence of close socio-cultural, economic and everyday contact of the Russian-Ukrainian population was also observed. The article is based on interdisciplinary research, at the intersection of ethnology, ethnography, and historiography. The methods of historical ethnography, historiographical analysis, and ethnological expertise are used. The scientific novelty lies in the formulation of the problem itself, since traditional settlements and dwellings of the northeastern Kazakhs were not previously considered as a problem in ethnology in the works of H. Argynbaev. It was revealed that in the process of ethnographic research, Khalel Argynbaevich substantiated his vision and conclusions, widely relying on a significant range of archival and written sources touching upon the problem in one aspect or another on the scale of the region under study.
Keywords: ethnography, Khalel Argynbayev, North-Eastern Kazakhstan, Kazakhs, Russians, traditional settlements, housing, cattle breeding.